Penerapan Pendekatan Teaching at The Right Level Berbantuan Media Quizizz untuk Meningkatkan Hasil Belajar Peserta Didik - Sumaryadi, Qurrotul Ayuni Rizqiyani; Astuti, Yuli; Novitasari, Dwi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to enhance the mathematics learning outcomes of Grade X-10 students at SMAN 6 Mataram through the implementation of the Teaching at the Right Level (TaRL) approach supported by the Quizizz learning platform. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The participants consisted of 36 students from Grade X-10 of SMAN 6 Mataram. The findings revealed a significant improvement in students’ academic performance. The average score increased from 60 in the pre-cycle to 75 in the first cycle and further improved to 84 in the second cycle. Similarly, the percentage of students achieving learning mastery rose from 28% in the pre-cycle to 61% in the first cycle and 78% in the second cycle. These results demonstrate that the application of the Teaching at the Right Level (TaRL) approach, combined with the continuous use of technology-based assessment tools such as Quizizz, can effectively and progressively enhance students’ learning outcomes.